Are high coronary risk patients missing out on lipid‐lowering drugs in Australia?. Issue 4 (18th August 2014) - Simons, Leon A; Chung, Eric
Abstract: Objective: To examine whether high coronary risk patients in Australia, where use of lipid‐lowering drugs (LLD) is very high by international standards, are receiving LLD. Design, setting and patients : Assessment of Pharmaceutical Benefits Scheme pharmacy payment claim records between January 2006 and May 2013 for a 10% random sample of Australian concession card holders. Co‐prescriptions were used as a surrogate for high coronary risk groups — coronary heart disease (CHD): antiplatelet drugs (not including solo aspirin) and anti‐anginal drugs; diabetes: all standard drugs; hypertension: all standard drugs (not including solo diuretics). Main outcome measure: Proportions of patients in high‐risk groups not receiving LLD (statins, fibrates or ezetimibe). Results: The database yielded information on 276 212 patients defined as being at high coronary risk (mean age, 66.1 [SD, 14.8] years; 44% male). Of this group, 115 477 patients (42%) had not received any LLD during the study period. For patients in the risk group for CHD in combination with diabetes and hypertension, only 8% (1111/14 257) were not receiving LLD. Across all risk groups, the proportions not receiving LLD were generally highest in those aged ≥ 81 years and, to a lesser extent, < 41 years, and were lowest in those aged 51–70 years. Conclusion: A large proportion of concession card holders at high coronary risk, especially those in middle age with CHD and multiple risk factors, are being appropriately prescribed LLD in Australia.